META-LEGAL BASIS OF THE AUTONOMY OF VOJVODINA BEFORE 1929 - Kovačev, Dušan (National interest, 2023)
Summary: The metalegal basis of the provincial autonomy of Vojvodina appeared in political form only after the state  fusion in 1918.  A cross-analysis of the material on Vojvodina political autonomysm points to its origin in the historical law of the Habsburg Empire, which was accepted by a group of few political outsiders and landowners of Vojvodina. The new modern state effectively and quickly solved problems: currency, tax and agrarian issues, improvement of trade, association and achieving sustainability of independent farms in Vojvodina. Then the Vojvodina autonomists looked for arguments in the backward standpoints of the past. The narcissism of cultural "superiority", negative prejudice against "Serbianci", the confusion of the concepts of regionalism, decentralization, autonomy and selfgovernment became the political material for the future metalegal construction of the autonomy of Vojvodina modeled on the "crownland" of the Habsburg real union. Already at the time of the fusion of Banat, Bačka and Baranja with Serbian, there were certain tendencys for the distinctiveness of the administration of these united area. At that time, happened first political attempts of a small number of politicians for the "State of Slovenes, Serbs and Croats" to recieve a certain role in the fusion of those areas with Serbia, by dint in Zagreb. In the area of Vojvodina, the right to selfdetermination of the people meant breaking the state ties with Hungary and fusion to  Serbia. For this purpose was formed the Great National Assembly of Serbs, Bunjevcis and other Slavs of Banat, Bačka and Baranja was formed. At the end of 1918, the Assembly elected by direct, equal and general suffrage of the population. This was the realization of the people's right to selfdetermination in a modern democratic form. The Assembly elected the administrative bodies of the temporary management of the area. Those bodies were not effective due to outdated understandings, unclear legal nature, and lack of distinction between administrative work, legal authorisation and legal competence. The problems caused by the temporary regional administration make dificults the subsequent work of the authorities of the Kingdom of Serbs, Croats and Slovenes, causing great intolerance towards "centralism". The government of the new state effectively solved administrative problems, currency, tax and agrarian issues under democratic conditions, and developed local selfgovernment. As the public became aware of the benefits of democratic modernity, general support for the new order grew. Opponents of the new order were a small number of nationalized landowners, economically stable officials and privileged individuals of the former Habsburg order. Among them, Serbian opposition politicians and Croatian nationalists sought support. Vojvodina's political autonomysm is from the beginning llinked to the political work of Croatian nationalists, the political fashion of "regionalism" and the historical sentiments of the Habsburg era. From the beginning formulated political ideas of Vojvodina autonomy, two phenomena stand out conspicuously: the support of Croatian nationalists and emotional intolerance towards Serbia and "Serbians". These phenomena are paradigmatically shown by two historical sources: Mihovil Tomandl's article "Serbian hegemony" (1923) and the proclamation of the Independent Democratic Party published under the title "Vojvodina wants to be its own" (1924).
Keywords: Vojvodina; autonomy; regionalism; decentralization; self-government; province